Khảo sát nhân lực ngành ngân hàng Việt Nam - Phạm, Thanh Bình (2011)
Tác giả: Phạm Thanh Bình, TS; Nguyễn Tư Nguyên; Phạm Tiến Đồng; Đỗ Thế Dân; Nguyễn Thanh Nguyên; Lê Phương Lan -- Từ khóa: Nhân lực; Ngân hàng